The role of the Entrepreneurial House in spreading entrepreneurial culture and thought in the university milieu as a tool to solve the problem of unemployment among university graduates - a case study of the Entrepreneurial House of Mila University Center - Bennoune, Khireddine; Bourihane, Farouk (Milev Journal of Research and Studies, 2018)
This Article aimed to clarify the role of Entrepreneurship House in dissemination the entrepreneurship culture in the universities, and try to find out the causes of high unemployment among graduate students, in order to make proposals to reduce them. The study focused on Entrepreneurship House at the university centre ABDULHAFID BOULOSOUF - Mila2 The descriptive approach was used by describing the most important concepts related to this study, and then presenting the important activities that were organized by Entrepreneurship House, and showing their impact on the dissemination the entrepreneurship culture at university centre ABDULHAFID BOULOSOUF – Mila. It was found that the main reason for the high unemployment rate among graduate students is due to the policy of the state in this field, in addition to the lack of awareness among students about the importance of investment orientation, and the necessary to adoption of entrepreneurial thinking as a new alternative to career, The Entrepreneurship House attaches great importance to spreading this awareness through the activities it organizes annually for the benefit of students.